The detection of prostate cancer based on ultrasound RF signal - Xiao, Tianlei; Shen, Weiwei; Wang, Qingming; Wu, Guoqing; Yu, Jinhua; Cui, Ligang (Frontiers in Oncology, 2022)
Objective The diagnosis of prostate cancer has been a challenging task. Compared with traditional diagnosis methods, the radiofrequency (RF) signal is not only non-invasive but also rich in microscopic lesion information. This paper proposes a novel and accurate method for detecting prostate cancer based on the ultrasound RF signal. Method Our approach is based on low-dimensional features in the frequency domain and high-throughput features in the spatial domain. The whole process could be divided into two parts: first, we calculate three feature maps from the ultrasound original RF signal, and 1,050 radiomics features are extracted from the three feature maps; second, we extracted 37 spectral features from the normalized frequency spectrum after Fourier transform. Results We use LASSO regression as the method for feature selection; moreover, we use support vector machine (SVM) for classification 10-fold cross-validation for examining the classification performance of the SVM. An AUC (area under the receiver operating characteristic curve) of 0.84 was obtained on 71 subjects. Conclusions Our method is feasible to detect prostate cancer based on the ultrasound RF signal with superior classification performance.